ETIKA MENUNTUT ILMU DALAM QS. THAHA AYAT 114: ANALISIS PEDAGOGI QUR’ANI UNTUK PENDIDIKAN MODERN - Amelina, Naila; Abdul Razzaq; Kristina Imron (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the ethical values ​​of seeking knowledge in QS. Thaha verse 114 and their relevance to strengthening modern pedagogy. This study uses a qualitative method with a library study type, which examines primary sources such as the Qur'an and tafsir books, as well as secondary literature related to Islamic education and contemporary pedagogical theory. The results of the study indicate that QS. Thaha verse 114 contains key values ​​that are highly relevant to today's education, namely the prohibition of haste in understanding knowledge, emphasizing the importance of patience, thoroughness, and a gradual process, the prayer "rabbi zidni ilma" reflects the principles of lifelong learning and intellectual humility. These values ​​have implications for the formation of teachers with integrity, reflection, and continuously developing their competence, as well as students who have a learning awareness, intrinsic motivation, and a polite scientific character. Thus, QS. Thaha verse 114 provides an important conceptual contribution to the development of more in-depth modern educational practices, and is rooted in Qur'anic values